Quality of life of Jordanian menopausal working and retired women and its associated factors: a cross-sectional study [version 1; peer review: 1 approved, 2 approved with reservations] - Mohannad AbuRuz; Sawsan Abuhammad; Muntaha K. Gharaibeh; Enas A. Assaf (F1000Research, 2022)
Objective: Life expectancy of Jordanian women has increased, indicating that the number of women entering menopausal age, during the prime of their working life, will also increase. Therefore, assessments of the quality of life (QoL) of working and retired women and factors associated with overall wellbeing, are essential for the provision of quality services and care. Method: A cross-sectional study was conducted with 200 Jordanian women between the ages of 45 to 60 years old.  The Utian QOL tool was used to assess the quality of life among menopausal women.  Multiple regressions were used to determine predictors for QoL for the whole sample and for each group of working and retired women. Results: The study shows that the total QoL for women was 77.5 ±14.4, with a significant difference (p=.023) in total QoL and the occupational domain (p=.003) between working and retired women. Employed women with fewer chronic diseases and using frequent preventive measures had a higher QoL compared to others. Conclusion: Working itself might be an important indicator for better a quality of life among menopausal women. Better working conditions and more attention from the health care providers for the menopausal changes and the preventive measures could enhance women’s perceived QoL in addition to increasing their productivity.